2019
DOI: 10.3389/fpls.2019.00565
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary Analyses Reveal Diverged Patterns of SQUAMOSA Promoter Binding Protein-Like (SPL) Gene Family in Oryza Genus

Abstract: The SPL ( SQUAMOSA promoter binding protein-like) gene family is one of the plant-specific transcription factor families and controls a considerable number of biological functions, including floral development, phytohormone signaling, and toxin resistance. However, the evolutionary patterns and driving forces of SPL genes in the Oryza genus are still not well-characterized. In this study, we investigated a total of 105 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 77 publications
4
25
0
Order By: Relevance
“…Gene duplication and syntenic analysis confirmed that no positive selection occurred in TaSPLs, additionally, TaSPL genes underwent strong purifying selection. Our results are consistent with the study of SPL genes in buckwheat [29] and rice [31], indicating that the evolution of TaSPL genes is comparable with that of other plants.…”
Section: Evolution Of Spl Family Genes In Wheatsupporting
confidence: 92%
See 1 more Smart Citation
“…Gene duplication and syntenic analysis confirmed that no positive selection occurred in TaSPLs, additionally, TaSPL genes underwent strong purifying selection. Our results are consistent with the study of SPL genes in buckwheat [29] and rice [31], indicating that the evolution of TaSPL genes is comparable with that of other plants.…”
Section: Evolution Of Spl Family Genes In Wheatsupporting
confidence: 92%
“…The ancestor SPL originally formed into two different lineages in land plants, named clade I and clade II. The clade I has conserved structure characteristics that possess more exons and longer protein sequences [31]. Our results showed that all SPL genes from wheat contained 1-11 exons.…”
Section: Evolution Of Spl Family Genes In Wheatmentioning
confidence: 68%
“…These results indicated similar gene numbers across a broad diversity of economically important grasses. In rice, a multitude of gene family members with high sequence similarity has been observed to cluster on the chromosomes as paralogous pairs [40,41]. However, we identified 12 OsDUF668s and found there were no collinearity relationships among them.…”
Section: Discussionmentioning
confidence: 70%
“…These results indicated that the domain organization has been constructed in the five Rosaceae species. These SBP domain locations, Zn1 and Zn2 binding sites, and NLS site were considered to be significant for specific recognition and binding to cis -elements in the promoter of nuclear genes [ 1 , 2 ]. Moreover, 11 SPLs belonging to the G10 group contain an ANK-2 domain ( Figure 4 ), which is associated with protein–protein interaction in plant cells [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…SPL protein contains the very conservative DNA-binding domain, namely the squamosa promoter binding protein (SBP) domain, consisting of ∼76 amino acid (aa) residues to carry out sequence-specific DNA binding and nuclear localization [ 1 ]. The SBP domain was composed of two zinc-binding sites (Cys–Cys–Cys–His and Cys–Cys–His–Cys) and a nuclear localization signal (NLS) partially overlapping with Cys–Cys–His–Cys [ 2 ]. Since 1996, SPL genes have been reported in many plants, such as Arabidopsis thaliana [ 3 ], rice [ 4 ], maize [ 5 ], Petunia [ 6 ], Dichanthelium oligosanthes [ 1 ], tea [ 7 ], Jatropha curcas [ 8 ], apple [ 9 ], pear [ 10 ], peach, and strawberry [ 11 ].…”
Section: Introductionmentioning
confidence: 99%